Contested Commitments: A Study of Homiletics Professors' Experiences with Diversity, Equity, and Inclusion (Homiletic, 2025)
Diversity, equity, and inclusion (DEI) are prominent topics of conversation in higher education, including seminaries and theological schools. The Academy of Homiletics DEI study, funded by the Wabash Center for Teaching and Learning in Theology and Religion, surveyed 81 professors, exploring the challenges and opportunities associated with incorporating DEI into their teaching of homiletics, the art of preaching. This phenomenological study, conducted in 2022, provides a mixed-methods analysis offering insight into the current state of DEI implementation in theological education, capturing a snapshot of the academic climate before the anticipated surge in opposition to DEI initiatives following the 2024 U.S. presidential election. The findings also provide a baseline to compare subsequent surveys as political and societal opposition to DEI initiatives intensifies across North America.